Concrete for transportation infrastructure proceedings of the international conference held at the University of Dundee, Scotland UK on 5-7 July 2005 - Dhir, Ravindra K.; McCarthy, Michael J. 1965-; Caliskan, Sinan (Thomas Telford, 2005)
The Concrete Technology Unit (CTU) of the University of Dundee organised this Congress to address the changes that are required to champion concrete and maintain its dominance within the global constructuion industry.